The Fourth Industrial Revolution: Conceptual paradox or catalyst for achieving the Sustainable Development Goals? - Mbiza, Mduduzi; Sinha, Saurabh (South African Journal of Science, 2023)
The topic of the Fourth Industrial Revolution (4IR) became significant in South Africa from 2017, through advocacy, amongst others, by the University of Johannesburg and subsequently through the appointment of the Presidential Commission on 4IR. Preceding industrial revolutions each focused on a single technology; 4IR, however, speaks to a confluence of technologies and a synergy of computing, data, and communications technology, with artificial intelligence rapidly redefining the world of work. Conceptual and geopolitical challenges and potential negative societal implications notwithstanding, we argue that the 4IR paradigm shift is critical to South Africa and to realising the Sustainable Development Goals.